2022
DOI: 10.2478/azibna-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary clove leaf meal supplementation: influence on egg qualities and reproductive morphometry of domestic laying birds

Abstract: This study investigated the effects of dietary Syzygium aromaticum supplementation on egg qualities, egg cholesterol and reproductive morphometry of laying hens. Three experimental diets were formulated containing 0.00%, 0.25% and 0.50% Syzygium aromaticum leaf meal (SLM). One hundred and fifty (20 weeks old) Isa-Brown birds were randomly assigned to three-treatment group which comprised 50 birds replicated five times with 10 birds each. Six eggs were collected from each replicate three days to the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…The reproductive tract morphometry was not statistically affected by the treatment effect in this study, suggesting that identical reproductive tract morphometry was triggered by the dietary supplementation of G-CLM in the laying hens. This thus contradicts the findings of Olateju et al (2022) who reported a significant increase in reproductive tract morphometry in ISA Brown pullets fed diets containing phytogenic addictive (Clove leaf meal).…”
Section: Discussioncontrasting
confidence: 99%
“…The reproductive tract morphometry was not statistically affected by the treatment effect in this study, suggesting that identical reproductive tract morphometry was triggered by the dietary supplementation of G-CLM in the laying hens. This thus contradicts the findings of Olateju et al (2022) who reported a significant increase in reproductive tract morphometry in ISA Brown pullets fed diets containing phytogenic addictive (Clove leaf meal).…”
Section: Discussioncontrasting
confidence: 99%